Healthcare in Ireland and Britain 1850-1970 Voluntary, regional and comparative perspectives - Lucey, Donnacha Seán (IHR Conference Series, 2015)
This volume explores developments in health and social care in Ireland and Britain during the nineteenth and twentieth centuries. The central objectives are to highlight the role of voluntarism in healthcare, to examine healthcare in local and regional contexts, and to provide comparative perspectives. The collection is based on two interconnected and overlapping research themes: voluntarism and healthcare, and regionalism/localism and healthcare. It includes two synoptic overviews by leading authorities in the field, and ten case studies focusing on particular aspects of voluntary and/or regional healthcare in Ireland and Britain.